PRE-CLINICAL EVALUATION OF LOWERING ATHEROSCLEROSIS RISK FACTORS IN HYPERCHOLESTEROLEMIC RATS AND THE IMMUNOMODULATING ACTION OF GANODERMA LUCIDUM AND CHRYSANTHEMUM INDICUM LINN - Bungihan, Melfei; Balonquita, Mark (MATTER: International Journal of Science and Technology, 2017)
This research aimed to address cardiovascular disease, specifically atherosclerosis, by using Ganoderma lucidum and Chrysanthemum indicum, and evaluate their immunomodulating action. Beta-glucans from G. lucidum and extract from flowers of C. indicum were used. Toxicological analysis was done. Biochemical factors in Rattus albus like serum total cholesterol, triacylglycerol (TAG), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C) were assayed. The rats were fed on high fat diet and induced with cholesterol, then treated with the different treatments. Immunomodulation was evaluated by measuring the immunoglobulins A, G and M on Escherichia coli- infected rats before and after treatment. For proliferation of lymphocytes, whole blood was collected on carrageenan inflammation-induced rats before and after treatment and determined through flow cytometry. Results show a decrease in the TAG (t=1.329,sig. 0.211), TC (t=4.956, sig. <0.0001), HDL-C (t= 0.486, sig. 0.636) and LDL-C (t=0.819, sig. 0.429) after treatment with the extracts but only the decrease in total cholesterol (TC) was significant at α 0.05. Paired t-test show a significant decrease in IgM (t= 2.969, sig. 0.013) and IgG (t= 3.865, sig. 0.003) while no significant decrease in IgA (t=1.683, sig 0.130). Comparison of the treatments using ANOVA showed significant differences between treatments in IgA (F(3,8) =8.458 , p = 0.007.) and IgG (F(3,8) =174.115, sig. <0.0001) but not significant in IgM (F(3,8) = 3.998 , p =.148). There was also significant increase in the number of lymphocytes on R. albus (t=2.659, sig. 0.019) but ANCOVA showed no significant differences in the different treatments (F=0.805, sig. 0.530) suggesting that all treatments were comparable in their effects in proliferating lymphocytes. It can be concluded that G. lucidum beta glucans and C. indicum flower extracts are safe and effective either as single dose or in combination in lowering atherosclerosis risk factors and in immunomodulation.